When Mothers Can't "Pay the Cost to Be the Boss": Roles and Identity within Doubled-Up Households. (18th June 2020) - Harvey, Hope
Abstract: Although the independent nuclear family remains the ideal family form in most Americans' minds, rising housing costs have made residential independence increasingly difficult. Sharing a home provdes a common safety net for lower-income mothers, yet we know little about how mothers experience and interpret this household form. Drawing on data from in-depth interviews with 52 mothers, I find that doubling up as a guest in someone else's home – though not hosting someone else in their home – threatens mothers' identities as adults and good parents. Mothers describe doubling up in someone else's home as incompatible with their ideals of adulthood and family life, which are organized around the independent nuclear family. While mothers expect to control their daily lives and childrearing, householders retain authority over the home and its inhabitants, and there is no taken-for-granted way of reconciling household members' conflicting expectations. In response to the stress on their identities, mothers who live doubled-up in someone else's home often seek to establish themselves as head of their nuclear family, even when they are not the household head, by engaging in identity work: defining physical space as their own, emphasizing their contributions to the household, and asserting their status as parents.